PENGARUH MOTIVASI, KEPUASAN, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI RRI SURAKARTA (Survei pada Pegawai RRI Surakarta) - Nugrahaningrum, Rosita Okta; Triastity, Rahayu; Sunarso, Sunarso (Universitas Slamet Riyadi, 2018)
This study aims to analyze the influence of motivation, satisfaction and work discipline together have a significant effect on the performance of RRI Surakarta employees partially and simultaneously. The population of this study was all RRI Surakarta employees using a sample of 44 respondents. Data collection techniques using questionnaire instruments through testing validity and reliability. Regression requirements test uses classic assumption test and Multiple Linear Regression Test, t test, F test and Determination coefficient (R2). The conclusion using the t test shows that motivation has a significant effect on the performance of employees at the RRI Surakarta, this is evidenced by the t test that produces a value of t = 2,467 > t table = 2,021. Satisfaction has a significant effect on the performance of employees at RRI Surakarta, this is evidenced by the t test that produces a value of t = 2,699 > t table = 2,021. Work discipline has a significant effect on the performance of employees at the RRI Surakarta, this is evidenced by the t test that produces a probability value of t = 3,967> t table = 2,021. Concluded that motivation, satisfaction and work discipline affect employee performance.Keywords: motivation, satisfaction, work discipline, employee performance